Optimal Design for the Lifting Gearbox of Self-elevating Offshore Platform - Zhang Qing; Li Ran; Zhang Xiaojie; Zhao Qianying; Qin Xianrong; Sun Yuantao (Jixie chuandong)
The lifting gearbox which is used on self-elevating offshore platform is selected as optimized object,its features and workings are introduced,and its reliability and mass are selected as optimization objectives,and the mathematical model is established for the optimization.A kind of coordinate its reliability and economy is proposed.By giving different values to the weighing factors to obtain different optimal solutions and fit a curve of them,the reliability and economy of the gearbox can be determined and coordinated.It is verified to be an effective method to acquire a higher cost-performance ratio of the gearbox,which may provide guidance for other similar engineering problems.